PERAN MANUSIA DALAM MEWUJUDKAN NEGERI YANG MAKMUR PERSPEKTIF AL-QUR’AN (STUDI TEMATIK) - Miftah Kalih Fajar; Pathur Rahman (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2021)
Al-Qur'an is a guide and source of human life. This holy book has provided a bright spot or explanation about the creation of the earth and everything in it for human needs. The creation of the earth as a space for human life to provide the needs where they live and to provide the survival of offspring. The Qur'an from time immemorial has emphasized that the entire universe was created for the benefit of all creatures. What is in nature, especially the earth, is an environment provided for all of God's creations that inhabit it, in this case especially human beings as the main creatures. This research is a library research, namely research conducted by examining library materials, especially verses of the Qur'an as primary data and books. The technique in this research is literature study, while the data collection is the primary approach. This research uses a normative approach, namely the library research approach, which is a form of research whose data is obtained from the library. At this stage the researcher looks for the theoretical basis of the research problem so that what is carried out is not a